THE ROLE OF MODERN INFORMATION TECHNOLOGY IN THE MANAGEMENT OF THE EDUCATIONAL PROCESS - Turdaliyev Sodikjon Muminjonovich (Galaxy International Interdisciplinary Research Journal, 2024)
This article revolutionizes the educational process in the digital age today by ensuring that information technology uses large resources and increases cooperation between students and teachers. In pedagogical education, from online educational platforms to interactive teaching tools, technology makes learning more interesting and accessible to students of all ages and all ages.